PENGARUH PENDIDIKAN MENGGUNAKAN AUDIO VISUAL TERHADAP PENINGKATAN PENGETAHUAN, SIKAP, DAN TINDAKAN PEMISAHAN SAMPAH PADA SISWA SD DI KOTA 19 KOTA BENGKULU - Aplina Kartika Sari; Vira Tika Yuniar; Sri Mulyati (Mitra Raflesia (Journal of Health Science), 2022)
Waste is something that is not used, not used, not liked or something that is discarded that comes from human activities and does not happen by itself. Waste sorting is the activity of grouping and separating according to the type of waste. Education or also called education is any planned effort to influence other people either individuals, groups, or the community so that they do what is expected by the education practitioners. Audio visual media is media that is able to display sound and images. This study aims to determine the Effects of Education Using Audio Visuals on Increasing Knowledge, Attitudes and Actions of Waste Sorting in Elementary School (SD) students in 19 Bengkulu City.This research method is a quasi experiment. The population of this study was 126 students who took 126 students in class V using simple random sampling and obtained 96 students consisting of class A 32 people, B 32 people and C 32 people. T-test statistical test results show the difference between knowledge, attitudes and actions before being given education and after being given education using audio visual (ρ = 0.00 <0.05).Conclusions there are significant differences between knowledge, attitudes and actions before and after being given education using audio visual.Keywords: audio-visual education, knowledge, attitudes, actions